Exclusion of the principle of non-refoulement in article 33 paragraph 2 of the 1951 refuge convention - Yatani, Vincent Godana; Safrin, Mohammad; Wagian, Diangsa (Ex Aequo Et Bono Journal Of Law, 2023)
This study aims to examine whether non-refoulement in the refugee context has attained the status of a jus cogens norm or not and how the exceptions in Article 33(2) should be understood if non-refoulement is indeed considered as a jus cogens. This research adopts a normative juridical analysis approach to critically examine the status of the principle of non-refoulement. The study concludes that the principle of non-refoulement qualifies as a norm of jus cogens based on several key criteria. Firstly, it satisfies the requirements of a jus cogens norm by addressing matters of common concern to the international community, serving humanitarian purposes, and aligning with principles outlined in the UN Charter relating to treaties and the use of force in international relations. Secondly, the exception outlined in Article 33 Paragraph 2 of the Refugee Convention does not alter the non-derogable nature of the principle of non-refoulement. The fulfillment of Article 33 Paragraph 2 is contingent upon strict conditions and necessitates objective evidence to be provided by a country. The research is intended to contribute to the understanding of the normative status of the principle of non-refoulement within the framework of international refugee law.